2002
DOI: 10.1046/j.1365-246x.2002.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and Mössbauer spectra of urban atmospheric particulate matter: a case study from Munich, Germany

Abstract: Summary Due to the high concentrations of iron in anthropogenically‐derived atmospheric particulate matter (PM), magnetic techniques are ideal for the study of the behaviour of PM. However, to undertake these studies it is necessary to have a thorough understanding of the magnetic mineralogy of PM. This study reports a detailed examination of the magnetic mineralogy of PM samples collected in Munich. Several different approaches have been utilized in the characterization; from standard mineral magnetic techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 74 publications
9
72
0
2
Order By: Relevance
“…Matzka and Maher (1999), Hoffmann et al (1999) and Moreno et al (2003) found that roadside pollution was mostly deposited within the first few metres from the road suggesting that the pollution is not evenly distributed. Muxworthy et al (2002) found no significant difference between PM collected 15 m and ~ 150 m from a road in central Munich.…”
Section: Discussionmentioning
confidence: 56%
“…Matzka and Maher (1999), Hoffmann et al (1999) and Moreno et al (2003) found that roadside pollution was mostly deposited within the first few metres from the road suggesting that the pollution is not evenly distributed. Muxworthy et al (2002) found no significant difference between PM collected 15 m and ~ 150 m from a road in central Munich.…”
Section: Discussionmentioning
confidence: 56%
“…The effective use of these methods in studying the urban pollution has been shown by more recent studies (e.g., Hoffmann et al, 1999;Matzka and Maher, 1999;Shu et al, 2000;Knab et al, 2001;Hanesch and Scholger, 2002;Muxworthy et al, 2002). These facts prompted us to undertake joint magnetic and geochemical investigations of urban materials (soil, road dust and tree-leaves) to address the environmental pollution of Kathmandu city, that has been subjected to environmental stress due to population overpressure and related urbanization.…”
Section: Introductionmentioning
confidence: 94%
“…Besides monitoring, we see an urgent need for characterization and quantification of the particles in differing environmental systems (atmosphere, soil, vegetation, water etc.) using rapid and cost-effective techniques, such as combined environmental magnetic and analytical chemical methods, similar to those applied in European countries (Petrovsky andEllwood, 1999, Hoffmann et al 1999;Hanesch and Scholger, 2002;Muxworthy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%